2021
DOI: 10.1093/ntr/ntab112
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Is Independently Associated With an Increased Risk for COVID-19 Mortality: A Systematic Review and Meta-analysis Based on Adjusted Effect Estimates

Abstract: Introduction Smoking can cause muco-ciliary clearing dysfunction and poor pulmonary immunity, leading to more severe infection. We performed this study to explore the association between smoking and mortality of coronavirus disease 2019 (COVID-19) patients utilizing a quantitative meta-analysis on the basis of adjusted effect estimates. Methods We conducted a systematic search of the online databases including PubMed, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Surprisingly current research on the relationship between smoking and SARS-CoV-2/COVID-19 has yielded conflicting findings [ 19 21 ]. For instance, a positive association between smoking and risk of COVID-19-related severe outcomes, hospitalization and death was found in some primary and secondary studies [ 22 – 25 ]. In contrast, other studies have identified lower proportions of active smokers among patients diagnosed with SARS-CoV-2 [ 26 29 ], and a significant lower prevalence of smoking among hospitalized COVID-19 patients than that expected on the basis of population smoking prevalence [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly current research on the relationship between smoking and SARS-CoV-2/COVID-19 has yielded conflicting findings [ 19 21 ]. For instance, a positive association between smoking and risk of COVID-19-related severe outcomes, hospitalization and death was found in some primary and secondary studies [ 22 – 25 ]. In contrast, other studies have identified lower proportions of active smokers among patients diagnosed with SARS-CoV-2 [ 26 29 ], and a significant lower prevalence of smoking among hospitalized COVID-19 patients than that expected on the basis of population smoking prevalence [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional concerns have been raised about the possible sources of residual confounding. Some studies relied on self-reported smoking habits and most failed to correct for relevant confounders which could result in different risk exposure while others combined current smokers and former smokers into one category, preventing from examining the interaction of SARS-CoV-2 with active smoking and its effect on risk of infection and COVID-19 outcomes [ 11 , 22 , 24 , 34 ]. As a whole, all these limitations reflect problems with poor reporting of the smoking status as well as lack of studies specifically designed to examine the association between smoking and COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its negligible effects on the expression of ACE2 and TMPRSS2 in endothelial cells [ 1 ], cigarette smoking is still associated with increased risk of severe COVID-19. On the basis of the results of a 2021 meta-analysis on more than 800,000 COVID-19 patients, smoking predicts a 19% increased risk of death in patients with COVID-19 [ 2 ]. Strangely enough, this increased severity does not manifest in the form of gross pulmonary damage that is typically revealed by imaging techniques [ 3 ].…”
Section: The Epigenetic Link Between Smoking and Covid-19mentioning
confidence: 99%
“…Since the beginning of 2020, when the COVID-19 pandemic outbreak took place, studies have delivered new evidence on the harmfulness of smoking—this time in the context of SARS-CoV-2 infection and the course of the COVID-19 disease. More and more research proves that smoking is an important risk factor contributing to increased risk of mortality among COVID-19 patients [ 9 ]. Research has shown that any history of smoking in the individual’s life is combined with a substantially higher vulnerability to severe course of the COVID-19 disease, as well as much worse prognosis in the event of hospital treatment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%